Managing health disasters and Civil–Military Cooperation: A case of COVID-19 in Pakistan - Rabeea Jabbar; Muhammad Makki (Jàmbá, 2021)
As an institution, the Pakistan Army has been playing a significant role in dealing with emergencies and disasters facing the nation. The novel coronavirus disease, Severe Acute Respiratory Syndrome (SARS) COVID-19, was wreaking havoc around the world. The pandemic is a threat to health and has caused severe damage across most aspects of the society. The situation forced the formation of a unique series of civil–military inter-agency relationships to be formed, in order to curb the spread of the pandemic. The Pakistan Army that was neither trained nor equipped to undertake any such health disaster management operation played a significant role in preventing disease and overcoming the disaster. Civil–military cooperation (CIMIC) was the key to the successful response of Pakistan towards COVID-19. The research was based on qualitative interviews that analysed the phenomenon of COVID-19 pandemic, that is, ‘health disaster’, to elucidate the disaster management practices performed through the framework of CIMIC in Pakistan. With regard to this, the article argued that formulating a comprehensive guideline or framework was necessary to maintain an effective and cooperative relationship between civil and military components. It further demonstrated the need to recognise the constitutive factors that influenced the functionalisation and institutionalisation of CIMIC to manage the highly complex health-related emergencies.